The Intergenerational Persistence of Self-Employment across China’s Planned Economy Era - Li, Minghao; Goetz, Stephan J. (Journal of Labor Economics, 2019)
Children whose parents were self-employed before China’s socialist transformation were more likely to become self-employed after the economic reform, even though they had no direct exposure to their parents’ businesses. The effect is statistically significant only for sons. The lack of direct exposure to family businesses impedes the transfer of business human capital and motivates us to explore personality traits as the underlying mechanisms. We find that children with self-employed parents are also more likely to invest in risky assets and to consume cigarettes. This suggests that children of self-employed parents inherit personality traits that induce risky behaviors.